(untitled) (Revista Puertorriqueña de Psicologia, 2019)
Ataques de nervios (ADN) is a cultural syndrome among Latinos characterized by emotional reactions triggered by upsetting interpersonal situations. ADN is highly comorbid with anxiety and trauma-related disorders. To date, it is unclear if ADN comorbidity brings additional difficulties in regulation and cognitive abilities. We compared if performance in cognitive tests differed among groups with anxiety disorders and group with co-morbid ADN using a Puerto Rican sample and how this related to associated psychological constructs. Methods: Participants were 19 subjects (12 with ADN) with an anxiety disorder. Spanish versions of the WAIS-III subscales, the WCST-IV, TMT, Stroop test, and RCFT assessed cognitive functions. Performance was then related to psychological constructs assessed by different self-report questionnaires, in both groups. Results: Subjects experiencing ADN showed decreased attention, concentration, and immediate memory. These differences were observed in their performance on the WAIS-III-Symbol Search sub-test (p=0.02) and the Rey-Complex Figure-Immediate Recall test (p=0.02). Conclusions: Individuals with co-morbid ADN showed worsened ability to concentrate, attend and retrieve information. Psychological constructs associated to the presence of ADN were correlated with worsened cognitive functioning. Further studies should be directed towards examining if this effect negatively impacts prognosis and treatment outcomes.